2022
DOI: 10.1016/j.jceh.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Pharmacological Validation of a Preclinical Model of NASH in Göttingen Minipigs

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Increasing studies indicate Göttingen Minipigs as an excellent translational model to study cardiovascular diseases [ 39 , 46 , 47 , 48 , 49 , 50 ], even in consideration of their propensity to develop various disorders of the metabolic syndrome, including obesity, insulin resistance, glucose intolerance, dyslipidemia, and atherosclerosis [ 39 , 51 , 52 , 53 , 54 , 55 , 56 ]. Clinical applications of mesenchymal stem-cell-based tissue engineering are promising due to the specific properties of these cells, i.e., high regenerative capacity, proliferative potential, immunomodulatory activity, and low immunogenicity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing studies indicate Göttingen Minipigs as an excellent translational model to study cardiovascular diseases [ 39 , 46 , 47 , 48 , 49 , 50 ], even in consideration of their propensity to develop various disorders of the metabolic syndrome, including obesity, insulin resistance, glucose intolerance, dyslipidemia, and atherosclerosis [ 39 , 51 , 52 , 53 , 54 , 55 , 56 ]. Clinical applications of mesenchymal stem-cell-based tissue engineering are promising due to the specific properties of these cells, i.e., high regenerative capacity, proliferative potential, immunomodulatory activity, and low immunogenicity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies indicate Göttingen Minipigs as an excellent translational model to study cardiovascular diseases [39,[46][47][48][49][50], even in consideration of their propensity to develop various disorders of the metabolic syndrome, including obesity, insulin resistance, glucose intolerance, dyslipidemia, and atherosclerosis [39,[51][52][53][54][55][56]. Clinical applications of…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Duvivier et al. reported that obeticholic acid administration for eight weeks in CDA‐HFD minipig model did not ameliorate MASH progression, but improved liver fibrosis 172 …”
Section: Non‐murine Models For Masld Evaluationmentioning
confidence: 99%